Massive Subchorionic Thrombohematoma (Breus’ Mole) Associated with Fetal Growth Restriction, Oligohydramnios, and Intrauterine Fetal Death - Miyuki Miyagi; Tadatsugu Kinjo; Keiko Mekaru; Hayase Nitta; Hitoshi Masamoto; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
Massive subchorionic thrombohematoma (MST), termed Breus’ mole, is a rare condition in which a large maternal blood clot separates the chorionic plate from the villous chorion. Common complications of MST include fetal growth restriction, preeclampsia, and intrauterine fetal death. Here, we present a case of a 17-year-old Japanese woman referred to our institution at 21 weeks of gestation. Ultrasound examination revealed a large placental mass with mixed high and low echogenicity measuring approximately 7.6 cm in thickness. Doppler examination showed absence of end-diastolic velocity of the umbilical artery. At 22 weeks of gestation, the patient had a stillbirth weighing 138g. The placenta weighed 502 g and was 8 cm thick, and the total blood loss was 270 g. Macroscopic examination revealed that a subchorionic blood clot measuring 12 cm × 5 cm covered a large portion of the placenta with well-defined margins on the fetal surface. Microscopic examination revealed an intervillous hematoma and fibrinous deposits directly beneath the chorionic plate with adjacent compressive effects. Based on these findings, MST was diagnosed. Because MST is rare, it must be considered in the differential diagnosis of parental conditions. Magnetic resonance imaging can be optimal for diagnosing MST when ultrasound diagnosis is difficult.